Stress and Efforts By Students in Learning During Covid-19 Pandemic - Mamnuah Mamnuah (Universitas Aisyah Pringsewu, 2021)
Students who experience stress during online learning are quite high. Stress will have an impact on student life in the future. For this reason, it is necessary to explore the stress experienced by students. The purpose of this study was to explore the stress and efforts made by health students in undergoing online learning. This research is qualitative with a phenomenological approach. The number of samples was 6 health students. Sampling was by purposive sampling. Data were analyzed using the Collaizi technique. The results showed that there were four themes of stress experienced by students, namely: perceptions of stress, feelings during stress, signs of stress symptoms, and causes of stress. The efforts made have two themes, namely: internal and external efforts. Students experience stress during online learning and make efforts to deal with the stress they experience. The results of this study provide important information for better learning management to anticipate student stress during the pandemic period.Abstrak: Mahasiswa yang mengalami stres selama pembelajaran daring cukup tinggi. Stres akan memberikan dampak dalam kehidupan mahasiswa di masa yang akan datang. Untuk itu perlu dilakukan eksplorasi tentang stress yang dialami mahasiswa. Tujuan penelitian ini adalah menggali stress dan upaya yang dilakukan mahasiswa kesehatan dalam menjalani pembelajaran daring. Penelitian ini adalah kualitatif dengan pendekatan fenomenologi. Jumlah sampel sebanyak 6 mahasiswa kesehatan. Pengambilan sampel dengan cara purposive sampling. Data dianalisis dengan menggunakan teknik Collaizi. Hasil penelitian menggambarkan stress yang dialami mahasiswa ada empat tema, yaitu: persepsi tentang stress, perasaan selama stress, tanda gejala stress, dan penyebab stress. Upaya yang dilakukan ada dua tema, yaitu: upaya internal dan eksternal. Mahasiswa mengalami stress selama pembelajaran daring dan melakukan upaya untuk mengatasi stress yang dialami. Hasil penelitian ini memberikan informasi penting untuk pengelolaan pembelajaran yang lebih baik untuk antisipasi stres mahasiswa selama masa pandemi.